What Determines Social Distancing? : Evidence from Advanced and Emerging Market Economies - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2021)
The health and economic consequences of COVID-19 are closely tied to individual compliance with recommended protective behaviors. We examine the determinants of this compliance using survey data from the COVID Behavior Tracker for 29 advanced and emerging market economies between March and December 2020. Social distancing behaviors vary significantly by age, gender, occupation, and individual beliefs about COVID-19. In addition, those who trust their government's response to COVID-19 are significantly more likely to adopt recommended behaviors and to self-isolate if advised, highlighting the need for well-coordinated actions on the health and economic fronts. We also find that mobility restrictions, such as stay-at-home orders, and mask mandates are associated with reduced social interactions and persistent increases in compliance. Together, these drivers account for over two-thirds of the regional differences in compliance, confirming their important role in increasing social distancing and containing the pandemic.